Assessment of serum zinc, copper and selenium in non sympotmatic sickle cell anaemia patients at the University Teaching Hospital, Lusaka, Zambia - Machiko, Alfred (Lusaka: University of Zambia, 2017)
Zinc, Copper and Selenium are important trace elements in human health and disease. They play a vital role as cofactors of enzymes such as superoxide dismutase and gluthione peroxide. They act as first line antioxidant enzymes in red blood cells and in plasma. In sickle-cell anaemia patients, the antioxidant activities of such enzymes is markedly reduced.Despite improvement in sickle cell anaemia management, morbidity and mortality still remains significant hence the need to assess their levels.
Thesis(Msc PATH)- University of Zambia,2017.
Includes bibliographical references.
Keywords: Sickle Cell Anemia; Drug Therapy